IL-6 During Influenza-Streptococcus pneumoniae Co-Infected Pneumonia—A Protector - Gou, Xuemei; Yuan, Jun; Wang, Hong; Wang, Xiaofang; Xiao, Jiangming; Chen, Jingyi; Liu, Shuang; Yin, Yibing; Zhang, Xuemei (Frontiers in Immunology, 2020)
Understanding of pathogenesis and protection mechanisms underlying influenza-Streptococcus pneumoniae co-infection may provide potential strategies for decreasing its high morbidity and mortality. Interleukin-6 (IL-6) is an important cytokine that acts to limit infection-related inflammation; however, its role in co-infected pneumonia remains unclear. Here we show that the clinically relevant co-infected mice displayed dramatically elevated IL-6 levels; which was also observed in patients with co-infected pneumonia. IL-6−/− mice presented with increased bacterial burden, early dissemination of bacteria to extrapulmonary sites accompanied by aggravated pulmonary lesions and high mortality when co-infection. This protective function of IL-6 is associated with cellular death and macrophage function. Importantly, therapeutic administration of recombinant IL-6 protein reduced cells death in BALF, and enhanced macrophage phagocytosis through increased MARCO expression. This protective immune mechanism furthers our understanding of the potential impact of immune components during infection and provides potential therapeutic avenues for influenza-Streptococcus pneumoniae co-infected pneumonia.